Benign hemorrhagic renal cyst mimicking cystic renal cell carcinoma - Fujii, Y (Hinyokika kiyo. Acta urologica Japonica, 1993)
We experienced four cases of benign hemorrhagic renal cyst which were indistinguishable from cystic renal cell carcinoma on ultrasonography, computer tomographic scanning, magnetic resonance imaging and angiography. Nephrectomy was performed in one case and enucleation of the mass in the other three. Pathological diagnoses were hemorrhagic septate cyst in two cases, cyst with inflammation containing old blood clots in one, and organized hemorrhagic cyst with calcification in one. Conservative surgeries should be considered when the definite diagnosis for renal hemorrhagic cysts is not made